Direct electrochemistry and electrocatalysis of hemoglobin on polypyrrole-Fe3O4/dodecyltrimethylammonium bromide-modified carbon paste electrode and its biosensing for hydrogen peroxide. (December 2013) - Zhou, Yuanzhen; Zhang, Haiyan; Zhang, Juncai; Zheng, Jianbin
Abstract A novel hydrogen peroxide (H2O2) biosensor was successfully constructed, based on the immobilization of hemoglobin (Hb) on polypyrrole (PPy)-Fe3O4 and dodecyltrimethylammonium bromide (DTAB) composite ﬁlm-modified carbon paste electrodes (CPE). The PPy-Fe3O4 composites were synthesized in the suspension solution of Fe3O4 nanoparticles via in situ chemical oxidative polymerization under the direction of cationic surfactant cetyl trimethyl ammonium bromide. Spectroscopic and electrochemical examinations illustrated that the PPy-Fe3O4/DTAB composites were a biocompatible matrix for immobilizing Hb, which revealed high chemical stability and excellent biocompatibility. The thermodynamic, dynamic, and catalytic performance of the biosensor were analysed using cyclic voltammetry (CV). The results indicated that the PPy-Fe3O4/Hb/DTAB/CPE exhibited excellent electrocatalytic activity in the reduction of H2O2 with a high sensitivity (104 μA mM− 1). The catalytic reduction currents of H2O2 were linearly related to H2O2 concentration in the range from 2.5 μM to 60 μM with a detection limit of 0.8 μM (S/N = 3). With such superior characteristics, this biosensor for H2O2 can be potentially applied in determination of other reactive oxygen species as well. These results indicated that PPy-Fe3O4/DTAB composites are a promising matrix for bioactive molecule immobilization.